1990
DOI: 10.1203/00006450-199009000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Ethanol Ingestion on Fetal Vitamin A in the Rat

Abstract: ABSTRACT. The effect of maternal ethanol ingestion on fetal tissue vitamin A was investigated. Pregnant rats were pair-fed control diets or diets containing 36% of energy as ethanol. After 17 or 21 d gestation, fetuses were removed and fetal and maternal tissues were analyzed by HPLC for retinol and retinyl palmitate. Ethanol consumption resulted in fewer fetuses per pregnancy, increased number of resorption~, and increased numbers of gross fetal abnormalities. In maternal tissues, ethanol consumption resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
(28 reference statements)
1
14
2
Order By: Relevance
“…The diet and feeding method are devised to ensure adequate and equivalent calorie, protein and general nutrient intake. Using this model, we have previously shown that ethanol consumption by the pregnant rat dam results in equal or only slightly reduced maternal weight gains for the first 19-20 days of gestation [17]. There is also no difference in the serum retinol concentrations between the pregnant dams consuming the control and ethanol diets [20].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The diet and feeding method are devised to ensure adequate and equivalent calorie, protein and general nutrient intake. Using this model, we have previously shown that ethanol consumption by the pregnant rat dam results in equal or only slightly reduced maternal weight gains for the first 19-20 days of gestation [17]. There is also no difference in the serum retinol concentrations between the pregnant dams consuming the control and ethanol diets [20].…”
Section: Discussionmentioning
confidence: 81%
“…The ethanol diet used was identical to that published previously [17,18]. Pregnant Sprague-Dawley (Harlan Industries, Indianapolis, Ind., USA) rats were randomly assigned to groups on gestational day 1 of pregnancy and kept in individual mesh-bottomed cages in a controlled temperature environment with a light-dark cycle of 12 h. The rats ate an isocaloric liquid Lieber-DeCarli diet by drinking from a Richter feeding tube (Dyets Inc., Bethlehem, Pa., USA), containing 25% protein, 63% carbohydrate and 12% fat.…”
Section: Ethanol Diet and Collection Of Tissuementioning
confidence: 99%
See 3 more Smart Citations